STRATEGI PEMBELAJARAN PAI BERBASIS DATA DAN BERKELANJUTAN (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the suboptimal implementation of Islamic Religious Education (PAI) in utilizing data and integrating sustainability principles. The purpose of this research is to analyze the implementation strategy of data-driven and sustainable PAI learning in improving learning quality and students’ character development. This study employs a qualitative approach using the library research method by reviewing various academic sources such as books, journal articles, and relevant educational documents. The results indicate that the integration of data-driven learning and Education for Sustainable Development (ESD) through the Plan–Do–Check–Act (PDCA) cycle produces more adaptive, effective, and long-term oriented learning. Data utilization supports accurate decision-making in teaching, while sustainability values strengthen character formation, including responsibility, social awareness, and environmental consciousness. The implementation is also supported by digital technology and innovative learning models that enhance student engagement and learning outcomes. The study concludes that data-based and sustainable PAI learning strategies play a significant role in improving learning quality and shaping students who are adaptive, responsible, and well-prepared for 21st-century challenges.